Brian De Palma's Split-Screen : A Life in Film - Keesey, Douglas (Book collections on Project MUSE., 2015)
Over the last five decades, the films of director Brian De Palma (b. 1940) have been among the biggest successes and the most high-profile failures in Hollywood history. Written in an accessible style, and including a chapter on every one of his films to date, this work is for anyone who wants to know more about De Palma's controversial films or who wants to better understand the man who made them.